Kurkumin Analog, PGV-0 dan GVT-0 Menghambat Absorpsi Kolesterol dengan Penghambatan Aktivitas Enzim Li - IKA PUSPITA SARI; ARIEF NURROCHMAD; IRFAN MURIS SETIAWAN; SARDJIMAN SARDJIMAN (Fakultas Farmasi Universitas Pancasila, 2013)
Curcumin has been known to reduce cholesterol levels in hyperlipidemic state. Faculty of Pharmacy Universitas Gadjah Mada (UGM) synthesized curcumin analogues namely PGV-0 and GVT-0. Like curcumin, both PGV-0 and GVT-0 exhibit anti-inflammatory activities. The aims of this study were to determine the effect and the mechanism of curcumin analogues PGV-0 and GVT-0 on regulation of cholesterol levels in serum. This study was aimed to examine whether PGV-0 and GVT-0 affected cholesterol levels through cholesterol absorption which is regulated by lipase enzyme. To determine the reduction in cholesterol levels, rats were feed with high fat diet (HFD) for 45 days. PGV-0 and GVT-0 were given on day 31-45 at doses of 40 mg/kg bw and 60 mg/kg bw consecutively. Total cholesterol and lipase activity in serum were measured and then statistically analyzed using ANOVA and t-test. The increase of cholesterol levels was markedly reduced by the treatment with both curcumin analogues. Furthermore, lipase activity was clearly inhibited by the treatment with PGV-0 and GVT-0, suggesting that these compounds inhibit cholesterol levels through the reduction of lipase enzyme activity